Culture D'Sabah Restaurant - Rostam, Norfazilah; Fredolin, Sueyane; Safri, Muhammad Faizal; Doksil, Marinah; Dullah, Nur Divya (2017)
Culture D'Sabah Restaurant is about providing products and services for Malaysian includes tourist that come to Sabah. Our business located Suria Sabah shopping mall, , 88000 Kota Kinabalu, Sabah. While there are many Malaysian restaurants everywhere, Culture D' Sabah only focus on Sabahan foods and it helps local supplier from remote village. Besides, Culture D'Sabah will slowly but surely gain market share as it provide Sabahan food to the Malaysian and tourist that in or just arrive in Sabah to get our first meal in the airport, and will creating long-term relationships with our customers. Moreover, we are believed that we will successfully compete with our competition in a few years ahead. This is because after do some research; we do not have any competitors in the airport unless a restaurant that provides fast food. Culture D'Sabahan aim is to get the Malaysian and tourist to get taste our meal before or after they in or out from airplanes. We, Culture D' Sabah, saw the opportunity that this business has the potential of success provided that it is handled efficiently. The people have always needed food to eat in thir life. This is because without food, we cannot live.